A novel approach to identify the best practices of quality management in SMES based on critical success factors using interpretive structural modeling (ISM) - Aich, Satyabrata; Muduli, Kamalakanta; Mehedi Hassan Onik, Md; Cheol Kim, Hee (International Journal of Engineering and Technology, 2018)
In recent years, most small and medium scale enterprises (SMEs) worldwide looking for improvement in their business practices in order to gain competitive advantage and total quality management(TQM) as a means by which SMEs could achieve the desired result. The objective of this study is to discover the critical success factors that are affecting the quality management practices in SMEs. In this work eight factors were identified through the literature review and experts from academic as well as industries. The factors are commitment to quality, employee involvement, customer focus, information technology, improved production planning and control, recognition system, supplier quality management, and management vision and mission. Interpretive structural modeling(ISM) is used to understand the complex relationships among the factors and classify the factors into various categories as per the driving and the dependence capacity. The result shows that information technology (IT) is a key success factor for implementing TQM in SMEs. It is observed that SMEs have to increase the use of IT to improve the quality of the product and productivity.Â Â